2020
DOI: 10.1021/acs.iecr.0c01665
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Effects of Ca2+, Mg2+, and SO42– on Calcite–Oil Interactions by “Soft Tip” Atomic Force Microscopy (AFM)

Abstract: The interactions of crude oil with calcite surface are influenced by the Ca2+, Mg2+, and SO4 2– ions in the aqueous solution in the context of wettability alteration and enhanced oil recovery; however, their effects are not well understood from the fundamental perspective. The force spectroscopy techniques that measure the attractive and repulsive forces between oil droplets and solid surfaces are crucial in developing this understanding. In this study, we investigated the effects of Ca2+, Mg2+, and SO4 2– ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 78 publications
1
11
0
Order By: Relevance
“…Therefore, in a macroscopic limit, treatment by Ca 2+ -rich saline solutions shifts the affinity of a calcite surface to a water-favoring state as frequently reported in previous conventional laboratory tests . This effect has been confirmed by the force spectroscopy technique in a recent study by Ding et al as well . They measured the interaction force of an oil droplet from a calcite surface and noticed the tendency of Ca 2+ cations for mitigating attraction force in a NaCl solution.…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, in a macroscopic limit, treatment by Ca 2+ -rich saline solutions shifts the affinity of a calcite surface to a water-favoring state as frequently reported in previous conventional laboratory tests . This effect has been confirmed by the force spectroscopy technique in a recent study by Ding et al as well . They measured the interaction force of an oil droplet from a calcite surface and noticed the tendency of Ca 2+ cations for mitigating attraction force in a NaCl solution.…”
Section: Discussionsupporting
confidence: 63%
“…More details on the relevant equations in the TLM model can be found in the literature. 34 , 78 , 85 The DLM presented in this work had been shown in our previous publications with all of the relevant reactions and equations. 11 , 19 , 27 …”
Section: Methodsmentioning
confidence: 99%
“…Second, when the [>CO 3 Ca + (−COO – )] and [>CO 3 Mg + (−COO – )] in the SW solution are used as references to evaluate the changes in cation-bridging interactions by other smart water (SWSO, SWCa, or SWMg solution), we find that (see Figure ) (a) [>CO 3 Ca + (−COO – )] increases significantly in SWSO solution, indicating an increased surface excess of Ca 2+ ions owing to the increase of [SO 4 2– ] in the aqueous solution, which causes a dramatic increase in the cation-bridging interactions between surface Ca 2+ ions and −COO – groups, resulting in strong and attractive calcite–oil interactions as well as huge adhesions in the SWSO solution, (b) [>CO 3 Ca + (−COO – )] and [>CO 3 Mg + (−COO – )] change equally but oppositely in the SWCa solution, while the strength of −COO – groups bridging with surface Ca 2+ ions is stronger than their bridging with surface Mg 2+ ions; thus, the decrease of [Ca 2+ ] in the aqueous solution has caused a decrease in the total cation-bridging interactions, generating repulsive calcite–oil interactions and small adhesions in the SWCa solution, and (c) [>CO 3 Ca + (−COO – )] increases substantially in the SWMg solution, indicating that a decrease of [Mg 2+ ] in the aqueous solution also causes an increase in surface excess of Ca 2+ ions, resulting in a dramatic increase in cation-bridging interactions between surface Ca 2+ ions and −COO – groups, hence introducing strong and attractive calcite–oil interactions and strong adhesions in the SWMg solution. In the end, it can be concluded that the SCM results highlight the importance of cation-bridging interactions (especially that between surface Ca 2+ ions and −COO – groups) as well as the ionic chemistry in determining the force behavior (attractive or repulsive) and force strength (e.g., adhesion and work of adhesion) of the calcite surface and crude oil, and, more importantly, the symbiotic effects of Ca 2+ , Mg 2+ , and SO 4 2– ions can be defined as a compensation relationship between Ca 2+ and SO 4 2– ions but a competition relationship between Ca 2+ and Mg 2+ ions (also see ref ), which lead to distinct force behaviors and force strengths in synthetic brines compared to those in single electrolytes (see ref ). Thus, the methodology of SCM might be a useful tool to optimize the ionic chemistry of smart waters to weaken the cation-bridging interactions and finally mitigate the attractions between the calcite surface and crude oil.…”
Section: Resultsmentioning
confidence: 93%
“…These types of tips have been used with AFM to measure the equilibrium or dynamic forces of the soft tip with a hard surface or another droplet (or gas bubble) in simple electrolytes (e.g., NaCl + sodium dodecyl sulfate (SDS) solutions), which inspired us to probe calcite–oil interactions first in single electrolytes of mediate concentration (e.g., 0.1 M CaCl 2 solution) and then in high-salinity smart waters in the context of enhancing oil recovery. In terms of the soft tip AFM study in single-salt solutions, it is interesting to find that Ca 2+ , Mg 2+ , or SO 4 2– separately had quite different impacts on the calcite–oil interactions: Ca 2+ decreased the calcite–oil attractions, Mg 2+ increased the calcite–oil attractions, and SO 4 2– changed the attractive calcite–oil interactions to repulsions . This preliminary study provides some hints for wisely manipulating the potential determining ions in injection water to promote the detachment of oil molecules from calcite surface, as well as on the optimal mechanical parameters of the AFM instrument to determine the intermolecular forces of a calcite surface with crude oil.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation